Union Budget Anomaly and Stock Market Reactions: A Study of Financial Services Sector Patterns - Jain, Ruchi; Arora, Jyoti (Journal of Neonatal Surgery, 2025)
Stock market anomalies occur when certain securities behave in ways inconsistent with the efficient market hypothesis, which suggests asset prices should reflect all available information. However, anomalies such as seasonal variations have been observed, contradicting this theory. Seasonal trends manifest as recurring stock price patterns within short time frames, often influenced by investor behavior, macroeconomic conditions, or major financial events. These trends are particularly visible in time series data, with fluctuations following consistent patterns during specific periods like month-ends, year-ends, or budget days. This paper investigates the 'Union Budget Effect,' a seasonal anomaly within the financial services sector. By analyzing Nifty Financial Services index data from 2016 to 2024, the study aims to determine if stock returns on budget days significantly differ from non-budget days. The findings offer insights into how budget announcements affect market performance, providing valuable knowledge for investors, fund managers, and policymakers. Understanding these effects can help stakeholders develop informed strategies, leveraging temporal variations to optimize returns and manage risks. Recognizing such patterns may improve portfolio management and enhance market timing strategies. This study highlights the significance of seasonal anomalies in financial analysis and investment planning